Low penetrance breast cancer predisposition SNPs are site specific. - Mcinerney, N; Colleran, G; Rowan, A; Walther, A; Barclay, E; Spain, S; Jones, A; Tuohy, S; Curran, C; Miller, N; Kerin, M; Tomlinson, I; et al. (2009)
Large scale association studies have identified low penetrance susceptibility alleles that predispose to breast cancer. A locus on chromosome 8q24.21 has been shown to harbour variants that predispose to breast, ovarian, colorectal and prostate cancer. The finding of risk variants clustering at 8q24 suggests that there may be common susceptibility alleles that predispose to more than one epithelial cancer. The aim of this study was firstly to determine whether previously identified breast cancer susceptibility alleles are associated with sporadic breast cancer in the West of Ireland and secondly to ascertain whether there are susceptibility alleles that predispose to all three common epithelial cancers (breast, prostate, colon). We genotyped a panel of 24 SNPs that have recently been shown to predispose to prostate, colorectal or breast cancer in 988 sporadic breast cancer cases and 1,016 controls from the West of Ireland. We then combined our data with publicly available datasets using standard techniques of meta-analysis. The known breast cancer SNPs rs13281615, rs2981582 and rs3803662 were confirmed as associated with breast cancer risk (P (allelic test) = 1.8 x 10(-2), OR = 1.17; P (allelic test) = 2.2 x 10(-3), OR = 1.22; P (allelic test) = 5.1 x 10(-2), OR = 1.15, respectively) in the West of Ireland cohort. For the remaining five breast cancer SNPs that were studied there was no evidence of an association with breast cancer in the West Ireland population (P (allelic test) > 6.5 x 10(-2)). There was also no association between any of the prostate or colorectal susceptibility SNPs, whether at 8q24 or elsewhere, with breast cancer risk. Meta-analysis confirmed that all susceptibility SNPs were site specific, with the exception of rs6983269 which is known to predispose to both colorectal and prostate cancer. This study confirms that susceptibility loci at FGFR2, 8q24 and TNCR9 predispose to sporadic breast cancer in the West of Ireland. It also suggests that low penetrance susceptibility SNPs for breast, prostate and colorectal cancer are distinct. Although 8q24 harbours variants that predispose to all three cancers, the susceptibility loci within the region appear to be specific for the different cancer types with the exception of rs6983269 in colon and prostate cancer.